Assessment of Mandibular Anterior Nutrient Canals in Patients with and without Periodontal Disease: A Cone Beam Computed Tomographic Study - Surekha Ramrao Rathod; Vrushali Lathiya; Yogesh Rathod; Ameya Bhide (Wolters Kluwer Medknow Publications, 2022)
Background: Nutrient canals (NCs) are radiolucencies in the bone that transit blood vessels and nerves. Aim: To use cone beam computed tomography (CBCT) to assess the incidence, diameter, and location of NC in healthy and periodontal disease patients and correlate it with the extent of alveolar bone loss. Materials and Methodology: About 200 CBCTs (100 healthy and 100 with periodontal disease) were selected and analyzed. The prevalence, diameter, and location of the NCs were comparatively evaluated between the two groups. The frequency and diameter of the canals were also correlated with the severity of bone loss, age, and gender. Results: Subjects in group II had a significantly greater frequency of NCs (P = 0.0001). NCs in group II had a larger mean diameter. The NCs were nearer to the alveolar crest in group II (16.70 ± 6.31 mm) than in group I (18.08 ± 5.72 mm). Their frequency was significantly greater when the bone loss was greater than two-thirds of the root length (P = 0.043). Conclusion: In patients with periodontal diseases, the incidence and diameter of NCs were higher and correlated positively with the extent of bone loss.